Social Adaptation of Immigrant Communities in Urban Communities - Abdul Malik Iskandar; Amir, Arfenti; Akhiruddin; Kasim, Hasanudin; Harifuddin; Herlina, Andi (Jurnal Multidisiplin Madani, 2023)
This article aims to analyze social adaptation and patterns of community social adaptation in the Manggarai migrant community in Nipa-nipa, Manggala Village, Manggala District, Makassar City. This research used a descriptive qualitative approach with informants from the Manggarai community, the local community and the head of the RT. Data collection was carried out by means of observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions. Researchers use triangulation to obtain data validity. Based on the research results, it can be concluded that 1) The reasons why the people of Manggarai urbanize are influenced by push factors from the village such as the lack of available jobs and lack of educational institutions, and pull factors from the city, namely the availability of jobs and the availability of educational institutions. 2) The social adaptation process of the Manggarai people, namely the Manggarai people use their reasons or goals as motivation to be able to adapt and maintain their attitudes and behavior, 3) The adaptation patterns they carry out are, namely, language adjustment patterns, norm adjustment and acting in accordance with positive things